2020
DOI: 10.1111/cas.14324
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of KIF3A inhibits triple negative breast cancer growth and metastasis by repressing Rb‐E2F signaling and epithelial‐mesenchymal transition

Abstract: Triple negative breast cancer (TNBC) displays higher heterogeneity, stronger invasiveness, higher risk of metastasis and poorer prognosis compared with major breast cancer subtypes. KIF3A, a member of the kinesin family of motor proteins, serves as a microtubule-directed motor subunit and has been found to regulate early development, ciliogenesis and tumorigenesis. To explore the expression, regulation and mechanism of KIF3A in TNBC, 3 TNBC cell lines, 98 cases of primary TNBC and paired adjacent tissues were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 55 publications
0
26
1
Order By: Relevance
“…In our study, we performed Western blotting and observed that the expression of the EMT-related proteins N-cadherin and Vimentin was downregulated after overexpressing KIF3A. However, in triple-negative breast cancer, knockdown of KIF3A expression reduced Vimentin protein expression and enhanced E-cadherin protein expression, which is contrary to our conclusion [13].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In our study, we performed Western blotting and observed that the expression of the EMT-related proteins N-cadherin and Vimentin was downregulated after overexpressing KIF3A. However, in triple-negative breast cancer, knockdown of KIF3A expression reduced Vimentin protein expression and enhanced E-cadherin protein expression, which is contrary to our conclusion [13].…”
Section: Discussioncontrasting
confidence: 93%
“…To date, KIF3A has been reported to function as a tumour promoter and to enhance the proliferation and metastasis of prostate cancer, triple-negative breast cancer, and bladder cancer [12][13][14]. Additionally, silencing the KIF3A gene in thyroid cancer cell lines leads to defective ciliogenesis, which in turn promotes mitochondria-dependent apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%
“… 30 Studies have demonstrated that the RB/E2F pathway is critical for control of the cell cycle and tumor progression. 31 , 32 pRB is phosphorylated on S807/811 during the S phase, and phosphorylation of RB's C-terminal serine (S795) destabilizes the interaction between RB and the E2F1-DP1 heterodimer. 33 , 34 Upon phosphorylation of RB at S795 and S807/811, downstream targets of E2F, such as CCNA2 , CDK1 , and MCM2 , will be transcriptionally activated.…”
Section: Discussionmentioning
confidence: 99%
“…The above experimental data confirmed that tRF-17-79MP9PP could inhibit breast malignant activities of cancer cells, so its target gene should be associated with tumor cell invasion, metastasis or proliferation. Based on the rationale, four candidate genes (THBS1, KIF3A, RAB10, RFX5) were selected after a literature review (18)(19)(20)(21)(22)(23). Further analysis revealed that tRF-17-79MP9PP had "seed sequences", which may bind to the 3'UTR of the four candidate genes according to TargetScan and miRanda programs (Figure 4B).…”
Section: Go and Kegg Enrichment Analysis Of Trf-17-79mp9pp Target Genesmentioning
confidence: 99%